Grand Canonical Monte-Carlo simulations for VOCs adsorption in non-polar zeolites. (16th April 2007) - Cosoli, Paolo; Ferrone, Marco; Pricl, Sabrina; Fermeglia, Maurizio
Removal of Volatile Organic Compounds (VOCs) by sorption in non-polar zeolite materials (AFR, BOG, LTL) has been tested by Grand Canonical Monte-Carlo (GCMC) molecular simulation techniques. Computational details and simulation procedure were validated by comparison with experimental data reported in literature. Results showed promising adsorption properties in the low pressure range. The adsorption isotherms for each single component could be obtained nicely by Langmuir equation. Molecular simulation techniques have proven to be a powerful tool to predict properties and suggest solutions, even in the relatively unexplored environmental field.